2014
DOI: 10.1021/pr500833v
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of High-Fat Diet on Metabolism and Immune Defense in Small Intestine Mucosa

Abstract: Improved procedures for sample preparation and proteomic data analysis allowed us to identify 7700 different proteins in mouse small intestinal mucosa and calculate the concentrations of >5000 proteins. We compared protein concentrations of small intestinal mucosa from mice that were fed for two months with normal diet (ND) containing 34.4% carbohydrates, 19.6% protein, and 3.3% fat or high-fat diet (HFD) containing 25.3% carbohydrates, 24.1% protein, and 34.6% fat. Eleven percent of the quantified proteins we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 45 publications
8
39
0
Order By: Relevance
“…[158][159][160][161][162][163] In contrast, stress, a high-fat diet, and glucocorticoids inhibit GLUT2 trafficking to the brush border membrane. [164][165][166] Most recently, subcellular localization studies using live cell imaging demonstrated that GLUT2 is endocytosed through a caveolae-dependent mechanism, which is partially recovered in Rab11A-positive recycling endosomes. 99 However, what is still not entirely clear is the role that this transporter plays while it is transiently expressed at the cell surface.…”
Section: Glut2 and Glut3mentioning
confidence: 99%
“…[158][159][160][161][162][163] In contrast, stress, a high-fat diet, and glucocorticoids inhibit GLUT2 trafficking to the brush border membrane. [164][165][166] Most recently, subcellular localization studies using live cell imaging demonstrated that GLUT2 is endocytosed through a caveolae-dependent mechanism, which is partially recovered in Rab11A-positive recycling endosomes. 99 However, what is still not entirely clear is the role that this transporter plays while it is transiently expressed at the cell surface.…”
Section: Glut2 and Glut3mentioning
confidence: 99%
“…High‐fat diet (HFD) feeding changes the functional properties of the small intestinal epithelium significantly. In particular enzymes involved in the fatty acid metabolism and oxidative phosphorylation pathways are substantially increased after 4 weeks of HFD exposure (de Wit et al, ; Wiśniewski et al, ). Also, we and others have shown that the systemic administration of fatty acid metabolism modulators induced an acute stimulation of fatty acid oxidation and ketogenesis in the jejunum but not in the liver (Uchida et al, ; Karimian Azari et al, ; Schober et al, ; Azari et al, ).…”
mentioning
confidence: 99%
“…turned out to represent cross-reactivity because they were removed after preabsorption of the antibody with the antigenic peptides but remained in SGLT1 À/À mice. Measuring SGLT1 mRNA abundance after TBI we ensured detection of SGLT1 specific signals although the abundance of SGLT1 mRNA in brain is four orders of magnitude lower compared to small intestine where SGLT1 is the most abundant transport protein in the brush-border membrane (Wisniewski et al 2015). Measuring mRNA abundance, we could relate the observed alterations to changes in transcription and/or mRNA stability.…”
Section: Discussionmentioning
confidence: 99%